Party politics in semi-democracies a comparative study of Bangladesh and Malaysia - Hasan, Moyenul; M, Moniruzzaman (IIUM Press, International Islamic University Malaysia, 2017)
The research book has found that both Bangladesh and Malaysia have maintained vibrant party systems throughout their history, though in the case of Bangladesh party politics have experienced military constraints for about a decade. Comparatively, Malaysian political parties maintain a better profile compared to their counterparts in Bangladesh. In terms of frequency in leadership change, the three older political parties in Malaysia have relatively frequent and regular leadership changes compared to the three Bangladeshi parties which have maintained very poor record.